Interaction of Hydrogen Sulfide with Nitric Oxide in the Cardiovascular System - Nagpure, B. V. (Oxid Med Cell Longev, 2016)
Historically acknowledged as toxic gases, hydrogen sulfide (H(2)S) and nitric oxide (NO) are now recognized as the predominant members of a new family of signaling molecules, “gasotransmitters” in mammals. While H(2)S is biosynthesized by three constitutively expressed enzymes (CBS, CSE, and 3-MST) from L-cysteine and homocysteine, NO is generated endogenously from L-arginine by the action of various isoforms of NOS. Both gases have been transpired as the key and independent regulators of many physiological functions in mammalian cardiovascular, nervous, gastrointestinal, respiratory, and immune systems. The analogy between these two gasotransmitters is evident not only from their paracrine mode of signaling, but also from the identical and/or shared signaling transduction pathways. With the plethora of research in the pathophysiological role of gasotransmitters in various systems, the existence of interplay between these gases is being widely accepted. Chemical interaction between NO and H(2)S may generate nitroxyl (HNO), which plays a specific effective role within the cardiovascular system. In this review article, we have attempted to provide current understanding of the individual and interactive roles of H(2)S and NO signaling in mammalian cardiovascular system, focusing particularly on heart contractility, cardioprotection, vascular tone, angiogenesis, and oxidative stress.